Analysis Of The Effect Of Job Demand Control-Support And Protection Motivation Towards Obedience With Filling In Medical Records At Batubara Hospital In 2021 - Bayu Ramazata; Ermi Girsang; Yolanda Eliza Putri Lubis (International Journal of Health and Pharmaceutical (IJHP), 2022)
A medical record is part of the archive that describes all activities by an agency within a certain period. Hospitals must have medical records as a service standard in the health sector that is useful for improving quality in providing optimal service to patients. The problem that often arises in filling out medical records is that in the process of filling it is incomplete, and the doctor's writing is less specific about the diagnosis. This situation has an impact on internal and external hospitals because the results of data processing are the basis for making hospital internal reports and hospital external reports. This study aims to analyze the effect of job demand control-support and protection motivation on Obedience with filling in inpatient medical record files at Batubara Hospital in 2021. This type of research is analytical quantitative research. The sample size in this study was 105 people. Data analysis used Univariate, Bivariate, and Multivariate. The results showed Job Demand Control-Support inpatient nurses at Batubara Hospital in 2021 were good as many as 94 respondents and 11 respondents were not good, Protection Motivation at Batubara Hospital in 2021 was good as many as 95 and 10 were not good, Obedience in filling out files inpatient medical records at the Batubara Hospital in 2021, which complied with as many as 94 respondents and 11 respondents who did not obey, Job Demand Control-Support affects Obedience with filling out medical record files for hospitalization at Batubara Hospital in 2021, Protection Motivation affects Obedience in filling out files Medical records for hospitalization at Batubara Hospital in 2021. The variable that has the most influence on Obedience with filling in inpatient medical record files at Batubara Hospital in 2021 is the Protection Motivation variable